The influence of demographics and comorbidity on persistence with anti-seizure medication. (April 2022) - Marshall, A.D.; Pell, J.P.; Askarieh, A.; Leach, J.P.; Heath, C.A.
Highlights: Persistence to anti-seizure medication affected by a range of factors. Younger and more deprived patients more likely to discontinue medication. Patients with higher rates of comorbidity or polypharmacy more likely to persist. Newer medications associated with higher rates of persistence compared to older. Abstract: Purpose: To examine the rate of persistence with anti-seizure medications (ASMs) in a cohort of patients with epilepsy, and to investigate the impact of a range of clinical and demographic factors on persistence Methods: Patients receiving ASMs for epilepsy were identified from linked, routinely collected data within the NHS Greater Glasgow and Clyde health board area between January 2011 and August 2019. Persistence with individual ASMs at 365-days after initiation was assessed using a 90-day allowable gap between individual prescriptions. Univariate logistic regression was used to estimate the association between 1-year persistence with ASM and demographic characteristics, comorbidities, and medication characteristics. Results: In total, 6, 449 patients with epilepsy were identified – 1, 631 were new users of ASMs at baseline and 4, 818 had been prescribed at least one ASM prior to baseline. Persistence with individual ASMs ranged 11.8% to 78.6%. Persistence was significantly lower in younger patients and patients who had previously been non-persistent to ASMs. Persistence was higher amongst those with cardiac comorbidities, previous stroke, or higher overall comorbidity, as well as those prescribed newer ASMs. Conclusion: Persistence varied widely. Demographic factors, previous non-persistence and overall number of comorbidities were more important determinants of persistence to anti-seizure medications than specific individual comorbidities. Interventions to improve persistence should be targeted at younger patients from more deprived backgrounds and those who have previously been non-persistent with ASMs.